Optical characterisation of InGaN-based microdisk arrays with nanoporous GaN/GaN DBRs. (23rd September 2022) - Fletcher, Peter; Martínez de Arriba, Guillem; Tian, Ye; Poyiatzis, Nicolas; Zhu, Chenqi; Feng, Peng; Bai, Jie; Wang, Tao
Abstract: Optically pumped whispering gallery mode (WGM) lasing has been observed in many freestanding microdisk structures. Dry etching is normally used to fabricate the microdisks, which causes severe sidewall damage, resulting in degradation of lasing performance, especially for ultra-small electrically-injected devices. In this paper, we demonstrate high quality microdisk cavities with 3.5 µ m diameter, by combining a selective overgrowth approach and an epitaxial lattice-matched distributed Bragg reflector (DBR), topped with a highly reflective (>99%) dielectric DBR. InGaN polaritons are found to occur in the high-quality microcavities. WGM modes are measured, with the positions in good agreement with finite difference time domain simulations. Furthermore, lasing behaviour is observed with a threshold at 410 µ W and a dominant mode at 488 nm.